Negative Regulation of Tumor Suppressor p53 by microRNA miR-504 - Hu, Wenwei (2010)
Tumor suppressor p53 plays a central role in tumor prevention. p53 protein levels and activity are under a tight and complex regulation in cells to maintain the proper function of p53. microRNAs play a key role in the regulation of gene expression. Here we report the regulation of p53 through microRNA miR-504. miR-504 acts as a negative regulator of human p53 through its direct binding to two sites in p53 3′-UTR. Overexpression of miR-504 decreases p53 protein levels and functions in cells, including p53 transcriptional activity, p53-mediated apoptosis and cell cycle arrest in response to stress, and furthermore, promotes tumorigenecity of cells in vivo. These results demonstrate the direct negative regulation of p53 by miR-504 as a mechanism for p53 regulation in cells, which highlights the importance of microRNAs in tumorigenesis.